PEMBELAJARAN TEMATIK BERBASIS REAL OBJECT DI SEKOLAH DASAR - Yeni Puji Astuti (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2018)
Permendiknas number 22 of 2006 which the states that the approach use teaching in elementary school low grade (grade I, II, and III) is a thematic learning. Learners class one, two, and three are in the range early age that they see everything as a whole (holistic) so that learning is still dependent on concrete objects and experiences that happened. Thematic learning with real object can help memory students last long, because the real object of abstract concepts could be real.